2016
DOI: 10.1097/01.epx.0000483164.17996.b8
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and factors associated with hepatitis C virus infection among patients with diabetes, Dammam, KSA

Abstract: The study confirmed a positive association between HCV and DM. The frequency of HCV among patients with diabetes was 1.9%. Predictors of HCV among DM patients were sharing articles, elevated transaminases, occupational exposure to blood or its products, disease duration more than 5 years, tattooing, blood transfusion, and hospitalization more than two times. We recommend screening for HCV among DM patients with elevated serum transaminases and those having the disease for more than 5 years and education of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
1
1
Order By: Relevance
“…Our result was slightly lower than that of Nigeria, 2009 (11%),17 India, 2016 (11%),18 Alger, 2012 (12.9%),19 and Pakistan, 2010 (13.7%),20 whereas it was much lower than reports from Iraq, 2015 (15%),21 DHQ teaching hospital, 2014 (27.38%)22 and Egypt, 2007 (32%) 23. On the other hand, a higher burden (7.5%) of HCV infection we found was higher compared to that of Sudan, 2014 (1.7%),24 Saudi, 2016 (1.9%),25 and Turkey, 2015 (3.8%) 26…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Our result was slightly lower than that of Nigeria, 2009 (11%),17 India, 2016 (11%),18 Alger, 2012 (12.9%),19 and Pakistan, 2010 (13.7%),20 whereas it was much lower than reports from Iraq, 2015 (15%),21 DHQ teaching hospital, 2014 (27.38%)22 and Egypt, 2007 (32%) 23. On the other hand, a higher burden (7.5%) of HCV infection we found was higher compared to that of Sudan, 2014 (1.7%),24 Saudi, 2016 (1.9%),25 and Turkey, 2015 (3.8%) 26…”
Section: Discussioncontrasting
confidence: 58%
“…Even though this study did not detect any significant epidemiological factors of HCV infection, other studies showed factors associated with HCV infections among DM patients. These included sharing materials, elevated transaminases, exposure to blood or its products, disease duration, tattooing, blood transfusion, and hospitalization more than two times.25…”
Section: Discussionmentioning
confidence: 99%